Dry matter productivity and bromatological quality of ryegrass genotypes cultivated in southern Brazil [Produtividade de matéria seca e qualidade bromatológica de genótipos de azevém cultivados no Sul do Brasil] - Ramos A.R. (2021)
© 2021. All Rights Reserved.The goal of this work was to assess the biomass production and bromatological quality of ryegrass genotypes in ten municipalities of the Western and North Plateau regions of the State of Santa Catarina, Brazil. The cultivars La Estanzuela 284 (diploid), Bar HQ, Barjumbo, INIA Escorpio, Potro, and Winter Star (tetraploids) were compared, distributed in a randomized block design, in which the municipalities constituted the blocks, with three replications. The cuts were performed when the plants reached 30cm, leaving a residue of 10cm. In three cuts, the cultivars Barjumbo and Bar HQ were the most productive, exceeding 4.6 t ha−1 of dry matter. In the places in which five cuts were performed, the production of these cultivars exceeded 7.3 t ha−1, placing them again ahead of the others. The average crude protein content in three cuts was greater than 25% in all cultivars. There was no difference between the genotypes in the content of neutral detergent fiber and total digestible nutrients. There was a significant correlation between quantitative and qualitative productive variables. The assessed cultivars represented good options for composing short-term or long-term winter-feeding systems, adjusted to the integration with annual crops or warm-season pastures.